xy + y = x + 2 giúp mình với
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
`@` `\text {Ans}`
`\downarrow`
\((x+y)(x-y)+(xy^4-x^3y^2) \div (xy^2) \)
`= x(x-y) + y(x-y) + xy^4 \div xy^2 - x^3y^2 \div xy^2`
`= x^2 - xy + xy - y^2 + y^2 - x^2`
`= (x^2 - x^2) + (-xy + xy) + (-y^2 + y^2)`
`= 0`
![](https://rs.olm.vn/images/avt/0.png?1311)
a,xy=2
=>x=2 ; y =1 hoặc x=1 ;y=2
b,xy=6
=>x=2;y=3 hoặc x=3 ; y=3
c,xy=12
=>x=2;y=6 hoặc x=6;y=2
=>x=3;y=4 hoặc x=4;y=3
d,xy=40 (x>y)
vì x>y
=>x=8;y=5
e,xy=30 (x<y)
vì x<y
x=5;y=6
![](https://rs.olm.vn/images/avt/0.png?1311)
a. Ta có : (x + y)[(x - y)2 + xy]
= (x + y)(x2 - 2xy + y2 + xy)
= (x + y)(x2 - xy + y2)
= x3 + y3
b. Ta có : x3 + y3 - xy(x + y)
= x3 + y3 - x2y - xy2
=x2(x - y) + y2(y - x)
= (x - y)(x2 - y2)
= (x - y)2.(x + y) đpcm
c) Ta có (x + y)3 - 3xy(x + y)
= (x + y)[(x + y)2 - 3xy)
= (x + y)(x2 + 2xy + y2 - 3xy)
= (x + y)(x2 - xy + y2) (đpcm)
a) VP = ( x + y )( x2 - 2xy + y2 + xy ) = ( x + y )( x2 - xy + y2 ) = x3 + y3 = VT ( đpcm )
b) VP = ( x + y )( x - y )2 = ( x + y )( x2 - 2xy + y2 ) = x3 - 2x2y + xy2 + x2y - 2xy2 + y3 = x3 + y3 - x2y - xy2 = x3 + y3 - xy( x + y ) = VT ( đpcm )
c) VP = x3 + 3x2y + 3xy2 + y3 - 3x2y - 3xy2 = x3 + y3 = ( x + y )( x2 - xy + y2 ) = VT ( đpcm )
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(x\left(xy+1\right)+y\left(xy-1\right)-xy\left(x+y\right)\)
\(=X^2y+x+xy^2-y-x^2y-xy^2\)
\(=x-y\)
![](https://rs.olm.vn/images/avt/0.png?1311)
sửa x^2 - x^2y + y^2 + 4xy
Thay x = 1 ; y = 2 vào ta được
\(1-2+4+8=11\)
![](https://rs.olm.vn/images/avt/0.png?1311)
xy+y=x+2
=>x=0
=>y=2
kick mik nha